2022
DOI: 10.1002/esp.5477
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic bedrock channel width during knickpoint retreat enhances undercutting of coupled hillslopes

Abstract: Dynamic bedrock channel width during knickpoint retreat enhances undercutting of coupled hillslopes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 57 publications
0
18
2
Order By: Relevance
“…According to a numerical study that considered the effects of sediment cover, channel narrowing occurs after the knickpoint passage, but as the knickpoint travels upstream the local sediment supply continues to increase, resulting in gradual widening of the channel (Yanites, 2018). A similar width adjustment was observed in a flume experiment (Baynes et al, 2022). Hillslope morphology is set by river incision at its base.…”
Section: Introductionmentioning
confidence: 75%
“…According to a numerical study that considered the effects of sediment cover, channel narrowing occurs after the knickpoint passage, but as the knickpoint travels upstream the local sediment supply continues to increase, resulting in gradual widening of the channel (Yanites, 2018). A similar width adjustment was observed in a flume experiment (Baynes et al, 2022). Hillslope morphology is set by river incision at its base.…”
Section: Introductionmentioning
confidence: 75%
“…The elevation of the valley floor in the trunk channel, due to overdeepening by ice, acts as a base level that the tributaries are adjusting to (Valla et al., 2010), and the zones of high K Sn are the knickpoints that separate the downstream reaches that adjusted to the new base level from upstream reaches that are typically low relief with low slopes (e.g., Figure 3b). We therefore hypothesize that the extent of postglacial fluvial adjustment (i.e., headward knickpoint retreat and corresponding channel and hillslope adjustment; Baynes et al., 2022) is an important control on the morphological impact of extreme events. As demonstrated here, the zone of potential sediment mobilization is much larger and located higher up in the catchment in Slei Gill compared to Grinton Beck where sediment mobilization is focused in the downstream reach only.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, channel width kept narrower after the passage of the knickpoints (Figures 4c and 4f). Baynes et al (2022) reported that the channel first narrowed and then became wider following the knickpoint passage. This shift from narrowing to widening corresponded with a transition from bed degradation to aggradation.…”
Section: Implications For Transient Responsementioning
confidence: 99%
“…Baynes et al. (2022) conducted flume experiments and reported width evolution during knickpoint retreat. They found that width decreased upstream of the knickpoint and reached the minimum at the knickpoint, and then increased after the passage of the knickpoint.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation